The Potential use of a Curcumin-Piperine Combination as an Antimalarial Agent: A Systematic Review - Shafia Khairani; Nisa Fauziah; Hesti Lina Wiraswati; Ramdan Panigoro; Endang Yuni Setyowati; Afiat Berbudi (Journal of Tropical Medicine)
Malaria remains a significant global health problem, but the development of effective antimalarial drugs is challenging due to the parasite’s complex life cycle and lack of knowledge about the critical specific stages. Medicinal plants have been investigated as adjuvant therapy for malaria, so this systematic review summarizes 46 primary articles published until December 2020 that discuss curcumin and piperine as antimalarial agents. The selected articles discussed their antioxidant, anti-inflammatory, and antiapoptosis properties, as well as their mechanism of action against Plasmodium species. Curcumin is a potent antioxidant, damages parasite DNA, and may promote an immune response against Plasmodium by increasing reactive oxygen species (ROS), while piperine is also a potent antioxidant that potentiates the effects of curcumin. Hence, combining these compounds is likely to have the same effect as chloroquine, that is, attenuate and restrict parasite development, thereby reducing parasitemia and increasing host survival. This systematic review presents new information regarding the development of a curcumin-piperine combination for future malaria therapy.